Electrodeposition-driven metal-support coupling in Pd-CeO2 on SiC monolith for low power Joule-heated CO oxidation - Lee, Hyunji; Kim, Jina; Kang, Sohyun; Kim, Kyung-Min; Jeon, Ye Eun; Kim, Ju Hwan; Kang, Dong Gwon; Han, Jeong Woo; Lee, Jungmin; You, Young-Woo; Kim, Seon Joon; Kim, Young Jin; et al. (Elsevier BV, 2025)
Low-power and fast-start oxidation over monolithic catalysts demands precise control over both interfacial architecture and spatiotemporally agile heat delivery, a combination rarely achieved by conventional slurry-coating and external heating (EH). Here we report a single-step electrodeposition strategy that simultaneously constructs metallic Pd nanoclusters and vacancy-rich PdxCe1−xO2−δ solid-solution domains on (111)-oriented ceria nanosheets grown across a Joule-heatable silicon carbide monolith. This electrodeposition-driven strong metal–support interaction (SMSI) preserves nanoscale Pd dispersion, enhances oxygen vacancy concentration, and facilitates rapid lattice–surface redox cycling for efficient CO oxidation. Under simulated exhaust conditions, the electrified monolith achieves complete low-temperature CO conversion with stable operation, outperforming a washcoated control that shows only partial and unstable activity. Direct Joule heating (JH) delivers fast, fully reversible thermal cycles with significantly reduced energy input compared to external heating, minimizing heat loss and localizing thermal energy at the active interface. By unifying synthesis, structure, and activation in a single electrically addressable platform, this work provides a scalable design strategy for next-generation electrified oxidation catalysts.